2007
DOI: 10.1682/jrrd.2006.09.0110
|View full text |Cite
|
Sign up to set email alerts
|

Assertive community treatmentIssues from scientific and clinical literature with implications for practice

Abstract: Abstract-This review describes Assertive community treatment (ACT), an integral component of the care of persons with severe mental illness. Drawing on research from North America, Australasia, and Britain, we summarize the current evidence base for ACT and examine the trends and issues that may affect practice. Strong evidence supports the fidelity standardization, efficacy, effectiveness, and cost-effectiveness of ACT models in psychiatry. Yet, significant methodological problems and issues affect implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 74 publications
3
55
0
11
Order By: Relevance
“…assertive mobile 7-day and night community-based mental health teams. [18][19][20] Further, community-based or domiciliary care [21][22][23] has been shown to be an important healing and abbreviating factor in aftercare following acute admissions for coronary care, strokes, renal dialysis, oncology, obstetrics, surgery and technical procedures of many types. 24,25 Health promotion, prevention, early detection and intervention Community Health Centres are the best local launching platform and base for health promotion, prevention and early intervention programs.…”
Section: Persistent Long-term and Recurrent Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…assertive mobile 7-day and night community-based mental health teams. [18][19][20] Further, community-based or domiciliary care [21][22][23] has been shown to be an important healing and abbreviating factor in aftercare following acute admissions for coronary care, strokes, renal dialysis, oncology, obstetrics, surgery and technical procedures of many types. 24,25 Health promotion, prevention, early detection and intervention Community Health Centres are the best local launching platform and base for health promotion, prevention and early intervention programs.…”
Section: Persistent Long-term and Recurrent Conditionsmentioning
confidence: 99%
“…However, the present growing demand for mental health inpatient beds could be effectively filtered by consistently placing in every catchment coherent, evidence-based, 24-hour mobile community assessment and acute care teams, community respite accommodation, mental health supported residential facilities, mobile assertive case management teams and rigorously organised GP shared care. 20,50,53 Evidence provided to the 'Not for Service' Inquiry 54 and the Australian Senate Select Committee Inquiry on Mental Health 55 indicated that even in states like Victoria, where crisis services had previously been most comprehensively implemented, psychiatric assessment services have since been concentrated in emergency departments. Consequently, there has been an increasing tendency to direct new referrals 'into these stressed environments, even during normal hours', where waiting times can be long, and service users find it difficult to contain their distress without disturbing others and often feel they must escalate life crises into life-threatening emergencies to be seen within living memory.…”
Section: The Lessons From Mental Health Servicesmentioning
confidence: 99%
“…ACTmodellen er også videreutviklet for integrert behandling både av psykose og rusmiddelproblemet ved kombinasjon av alvorlig psykisk lidelse og alvorlig rusmiddel problem. ACT er en effektiv form for psykososial behandling for de dårligste pasientene med schizofrenidiagnose, som ellers ville ha vaert innlagt over lang tid (446). Hvorvidt slike team også reduserer innleggelser i spesialisert psykisk helsevern, er uklart, men noen studier peker i den retningen (447).…”
Section: Act-team -Assertive Community Treatment 1aunclassified
“…On souligne aussi la quasi absence de re cherches qui tiennent compte des enjeux cliniques associés aux diverses approches du traitement (Burns, 2008). Pour combler ces lacunes, des études plus récentes abordent les enjeux éthiques des interventions (Szmukler, 1999), par exemple : le partage de l'information et la confidentialité (Chen, 2008), la coercition dans le suivi (Appelbaum et Le Melle, 2008 ;McGrew et al, 2002 ;Molodynski, 2010 ;Rosen et al, 2007), le rapport à la médication (Tam, 2007), l'alliance thérapeutique (Howgego et al, 2003), le rapport aux proches et la confidentialité ainsi que la diversité de finalités associées à la notion d'intégration sociale selon les acteurs (Ware, 2007).…”
Section: Tableau Iunclassified